A Modified Class III Activator in the Treatment of Anterior Crossbite - Özge Uslu (Galenos Yayinevi, 2007)
In the current study, the treatment of a male individual (9.9 years) having anterior cross-bite, maxillary retrusion and functional Class III malocclusion treated by modified Class III activator was presented and the results were discussed. A mini screw was involved to the modified Class III activator for premaxilla and upper incisor protrusions and the activation was set as 2 times a week. Anterior crossbite was eliminated and a Class I occlusion was achieved at the end of 11 months treatment period.